Radio-frequency connectors. RF coaxial connectors with inner diameter of outer conductor 1, 85 mm (0, 072 in) with screw coupling. Characteristic impedance 50 ohms (type 1, 85) Part 32, (15th January 2000) - British Standards Institution,
No abstract available